PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TAKING DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX MTsN BUNGUS TELUK KABUNG PADANG - Kumala Dewi, Silvi; Rahmi, Rahmi; Pratiwi, Merina (Pendidikan Matematika, 2014)
ABSTRACTThe aim of this research was to reveal whether the understanding of Â mathematical concept by using Guided Note Taking active learning model was better than by using conventional model. This was an experimental research which used random toward the subject desaign. The population of the research was the student in class IX of MTsN Bungus Teluk Kabung Padang in Academic Year 2012/2013. The instruments of the research were a quiz and a post-test. The data gathered was analyzed by using t-test. Basade on the result of data analysis it was found that the average score of the student in the experimental class (86,37) was higher than those in the control one (78,90). The result of hypothesis test indicated that P-value was smaller than Î±. Therefore, it was concluded that the understanding of mathematical concept by using Guided Note Taking active learning model was better than by using conventional learning.